2008
DOI: 10.1097/acm.0b013e3181723095
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Assessment of an NIH-Funded Research Ethics Training Program

Abstract: In an effort to increase the number of researchers with skills "in identifying and addressing the ethical, legal, and social implications of their research," the National Institutes of Health (NIH) solicited training grant proposals from 1999 to 2004 and subsequently funded approved programs. The authors describe the content, format, and outcomes of one such training program that ran from 2002 to 2006 and share key lessons learned about program formats and assessment methods. Jointly developed by the Saint Lou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…20 However, surveys of trainees and early-and midcourse scientists who have taken such courses have found that although these programs increased the participants' knowledge of ethical issues and their ability to identify them, they were unlikely to affect their future behavior. 3,[21][22][23][24] As simply stated by a participant in one of these studies: "In most cases, I believe a person is ethical or not. I feel that if a person chooses to do something unethical it's not because they never took an ethics class."…”
Section: Introductionmentioning
confidence: 97%
“…20 However, surveys of trainees and early-and midcourse scientists who have taken such courses have found that although these programs increased the participants' knowledge of ethical issues and their ability to identify them, they were unlikely to affect their future behavior. 3,[21][22][23][24] As simply stated by a participant in one of these studies: "In most cases, I believe a person is ethical or not. I feel that if a person chooses to do something unethical it's not because they never took an ethics class."…”
Section: Introductionmentioning
confidence: 97%
“…Artino (2009a) and DuBois et al (2008) observed using an experiment that a lack of interaction results in a decrease in engagement and satisfaction and an increase in drop-out risk. In summary, it can be observed that the publications retrieved report positively on the influence of social interaction for increasing cognitive (e.g., Siampou et al 2014), metacognitive (e.g., Kuo et al 2012) and motivational e.g., Lin et al (2012) learner variables.…”
Section: Interactionmentioning
confidence: 99%
“…We retained 70 publications that appear to centre around interaction (e.g., Alant and Dada 2005;Chen 2014;Clark et al 2015;DuBois et al 2008;Gomez et al 2010;Ho and Dzeng 2010;Liaw et al 2010;Lin et al 2012;Ma 2012;Siampou et al 2014;Ting 2013;Xie et al 2013). These publications describe interaction as the involvement of learners with elements in the learning environment, including content (learning materials, object, etc.…”
Section: Interactionmentioning
confidence: 99%
“…In analytical ethics-education programs, ethical issues are not held to be fully defined by the profession 8,9 . Thus, in these programs,…”
Section: Analysis Programsmentioning
confidence: 99%